On the trophic role of pelagic fishes and fishery landings shifts in the South Brazil Bight - Julia Petroski Olher; Maria A. Gasalla (Ocean and Coastal Research)
Knowledge of the feeding habits of pelagic fishes off the Brazilian coast is scarce, making the analysis of trophic interactions often inaccurate. Here, we investigated the diet and trophic role of 12 pelagic fish species by revisiting samples obtained by the ECOSAR II Program (FURG/IO/IBAMA) between 23°S and 28°40'S, an area also known as South Brazil Bight. In addition, we analyzed their biomass and fisheries landings in order to examine shifts over time. The content of 432 stomachs was analyzed at the lowest taxonomic level possible. The frequencies of occurrence were used to cluster species, revealing three trophic guilds: "Planktivorous Clupeiformes", "Planktivorous Carangiformes", and "Piscivores". Most Carangidae consumed mainly copepods and other small crustaceans, except Selene setapinnis which clustered in the piscivorous guild together with Scombriformes specimens. In terms of biomass, the dominance of Trachurus lathami, Sardinella brasiliensis, and Trichiurus lepturus was evident. The species' trophic levels ranged from 2.98 to 4.5, showing that these fishes occupied intermediate to high trophic position. Comparing fisheries landings in two study periods (1986-2002 and 2003-2019), six species showed a decrease, while three an increase. Correlations between landings of the Brazilian sardine (Sardinella brasiliensis) and other pelagic fishes indicate that when the former's decreases, the catch of alternative species, such as Opisthonema oglinum and Chloroscombrus chrysurus, increases. The intermediate position of small pelagics in the food web may affect the availability of commercial species by controlling the abundance of lower and upper trophic-level organisms. These findings fill essential gaps for ecosystem modeling, suggesting that ecosystembased fisheries management should address multispecies issues of the pelagic realm rather than only singlespecies approaches. Combining past survey data with yield trends provides evidence for both natural and humaninduced ocean changes.